Magnetic resonance spectroscopy measurements of intragastric fat fraction of oil emulsions in humans. Issue 1 (26th August 2014) - Hussein, Mahamoud O.; Hoad, Caroline L.; Stephenson, Mary C.; Cox, Eleanor F.; Placidi, Elisa; Pritchard, Susan E.; Costigan, Carolyn; Ribeiro, Henelyta.; Ciampi, Elisabetta; Rayment, Pip; Nandi, Asish; Hedges, Nick; et al.
<x xml:space="preserve">Abstract</x> There is considerable interest in manipulating the behavior of dietary emulsions in the human stomach as a means of altering satiating properties of fatty foods. However assessing this using intubation markedly disturbs normal gastric motility so a non‐invasive imaging approach has a strong rationale. Two 20% sunflower oil‐in‐water fat emulsions test meals with different droplet sizes (termed Fine and Coarse) and intragastric behaviors were used to demonstrate, for the first time, the feasibility of carrying out magnetic resonance spectroscopy (MRS) measurements of fat emulsions fat fraction, in vivo, in the gastric lumen of six healthy volunteers. Magnetic resonance imaging (MRI) confirmed that as expected the fine emulsion remained mostly homogeneously distributed inside the stomach over the course of 3 h but the Coarse quickly creamed showing an upper layer much richer in fat. The MRS measurements showed that the Coarse emulsion had an upper layer of high lipid/water ratio compared to the lower layer. The fine emulsion fat fraction values remained stable throughout the study with no difference between upper and lower layers. It is therefore possible to quantify in vivo, in the gastric lumen, the intragastric fat fraction of oil‐in‐water fat emulsions using non invasive MRS techniques. Practical applications: This study shows that it is possible to quantify in vivo, in the gastric lumen, the intragastric fat fraction of oil‐in‐water fat emulsions using non invasive magnetic resonance spectroscopy techniques. These measurements can help improve understanding of intragastric distribution of fat, its relation to satiety, can improve the relevance of in vitro/in vivo models of fat digestion, and will ultimately aid the design of foods with desired health promoting characteristics and check their performance in vivo. <inline-graphic xlink:href="ark:/27927/pgh30vn1pgr" content-type="ejlt201400058-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Two 20% sunflower oil‐in‐water fat emulsions test meals with different droplet sizes and intragastric behaviours are used to demonstrate, for the first time, the feasibility of carrying out magnetic resonance spectroscopy (MRS) measurements of fat emulsions fat fraction, in vivo, in the gastric lumen of six healthy volunteers.